Social Impact Assessment of the Desa Brilian Program Using the Social Return on Investment Method and Community Satisfaction Index - Dinne Shovia Tresna Amalia; Agustya Hendy Bernadi; Agusman Muhammad Latif (Green Publisher Indonesia, 2025)
The BRILiaN Village Empowerment Program is a corporate social and environmental responsibility initiative implemented by PT Bank Rakyat Indonesia (Persero) Tbk from 2021 to 2024. This program aims to strengthen rural development through training, infrastructure assistance, and business cluster development. Over its four-year implementation, the program has generated tangible impacts on local communities. To evaluate its effectiveness, an impact assessment was conducted using the Social Return on Investment (SROI) methodology combined with the Indeks Kepuasan Masyarakat (IKM). This dual approach provides multidimensional analysis, not only quantifying the social value created but also capturing beneficiaries’ satisfaction. The SROI analysis produced a ratio of 2.31, meaning that every IDR 1 invested generated IDR 2.31 in social value. Meanwhile, the IKM result reached 85.53%, categorized as “good,” reflecting high community satisfaction. The findings highlight that integrating SROI with IKM offers a comprehensive framework to measure the impact of CSR-based empowerment programs, ensuring that social, economic, and community perspectives are equally represented.